ANALISA PERBANDINGAN KEKERASAN PAVING DENGAN CAMPURAN ABU BATU DAN PASIR - Ahmad Susanto; Achmad Akbar Romadhon; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
Paving block is an environmentally friendly construction where paving blocks are very good at helping groundwater conservation, implementation is faster, easy to install and maintain, has a variety of forms that add aesthetic value, and the price is easy to reach. Therefore, paving blocks are an important building material in the construction of public facilities, especially for road construction in residential areas. The use of paving blocks in the field is still limited to parking lot pavements, sidewalks, parks and connecting buildings. Even though the application of paving block materials is very wide. However, of course, local experience and the successful use of paving blocks will play more and more influence in terms of the application of these materials. Stone ash in this study was used as a substitute for natural fine aggregate (natural sand) with the proportions of 0%, 15%, 30%, 45%, and 60%. To get the optimal compressive strength value, the researcher has the opinion of a combination of fine aggregate of natural sand and rock ash waste with the appropriate percentage. And tested with mortar age of 14 days and 28 days. In the study, the volume weight test of paving blocks with the addition of stone ash waste obtained the highest compressive strength at a variation of 45% for the test at the age of 14 days and 28 days, with the compression test for 14 days reaching a compressive strength of 100.92 kg/cm2 and for the compressive test 28 day reached a compressive strength of 160.28 kg/cm2.